2021
DOI: 10.1027/2512-8442/a000085
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Mindfulness Facets and Mental and Physical Health in Meditating and Nonmeditating University Students

Abstract: Abstract. Background: Little is known about the relations of the mindfulness facets to mental and physical health among meditators and nonmeditators. Aim: The main purpose of the present study was to investigate the relationship between the mindfulness facets and mental as well as physical health of university students with and without meditation experience using attentional control, body awareness, nonattachment, and emotion regulation as mediators. Method: Data were collected from a sample of 508 university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Baer [36] argued that people without meditation experiences might observe the present judgmentally and impulsively, whereas practitioners might observe with openness and acceptance, in this study we found a positive link between observing and depressive symptoms among practitioners with a regular meditation practice (See [46] and [37] for similar findings). In addition, our SEM findings revealed that observing was not related to nonjudging of inner experience at all (see Fig 1).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Baer [36] argued that people without meditation experiences might observe the present judgmentally and impulsively, whereas practitioners might observe with openness and acceptance, in this study we found a positive link between observing and depressive symptoms among practitioners with a regular meditation practice (See [46] and [37] for similar findings). In addition, our SEM findings revealed that observing was not related to nonjudging of inner experience at all (see Fig 1).…”
Section: Discussionsupporting
confidence: 76%
“…However, a study reported that observing was related to greater rumination and lower attentional control, and that the indirect links between observing and mental/physical health complaints via greater body awareness and nonattachment were significant among samples with or without meditation experience [37]. As such, the association between observing and well-being among meditators and non-meditators remain inconsistent and unclear.…”
Section: Differential Contributions Of the Facets Of Mindfulnessmentioning
confidence: 99%
“…The EffectLiteR approach has been successfully applied to analyze average and conditional effects in various substantive examples especially from clinical psychology and educational science. For example, it has been used to estimate the effects of an autonomy-supportive intervention for teaching physics lessons in high school (Flunger, Mayer, & Umbach, 2018; Mayer, Umbach, Flunger, & Kelava, 2017), for analyzing the effects of inpatient psychotherapy on attachment characteristics (Kirchmann et al, 2011), for examining early transition to secondary school compared to late transition (Mayer, Nagengast, Fletcher, & Steyer, 2014), for evaluating a stress prevention program with teacher students (Karing & Beelmann, 2016), and for looking at differential effects of reading trainings on reading processes (Müller et al, 2015). Most of these examples include either latent covariates or latent outcome variables in the statistical model.…”
Section: Models For Causal Effectsmentioning
confidence: 99%
“…Although previous studies have shown that mindfulness is related to body awareness and non-attachment, and both seem to be mediators in the relationship between mindfulness and mental health ( Burzler et al, 2019 ; Karing et al, 2021 ), only a few studies have investigated the effect of mindfulness training on these constructs ( Beshai et al, 2020 ; Karing and Beelmann, 2021 ). Non-attachment is described as a flexible, balanced way of relating to one’s experiences and not cling to or avoiding such experiences ( Sahdra et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%